Stroke-Specific Quality of Life one-year post-stroke in two Scandinavian country-regions with different organisation of rehabilitation services: a prospective study - Pedersen, Synne Garder; Friborg, Oddgeir; Heiberg, Guri Anita; Arntzen, Cathrine; Holm Stabel, Henriette; Thrane, Gyrd; Nielsen, Jørgen Feldbæk; Anke, Audny (Disability and Rehabilitation, 2020)
Purpose: To compare stroke-specific health related quality of life in two country-regions with organisational differences in subacute rehabilitation services, and to reveal whether organisational factors or individual factors impact outcome. Materials and methods: A prospective multicentre study with one-year follow-up of 369 first-ever stroke survivors with ischaemic or haemorrhagic stroke, recruited from stroke units in North Norway (n = 208) and Central Denmark (n = 161). The 12-domain Stroke-Specific Quality of Life scale was the primary outcome-measure. Results: The Norwegian participants were older than the Danish ( M age = 69.8 vs. 66.7 years, respectively), had higher initial stroke severity, and longer stroke unit stays. Both cohorts reported more problems with cognitive, social, and emotional functioning compared to physical functioning. Two scale components were revealed. Between-country differences in the cognitive-social-mental component showed slightly better function in the Norwegian participants. Depression, anxiety, pre-stroke dependency, initial stroke severity, and older age were substantially associated to scale scores. Conclusions: Successful improvements in one-year functioning in both country-regions may result from optimising long-term rehabilitation services to address cognitive, emotional, and social functioning. Stroke-Specific Quality of Life one-year post-stroke could be explained by individual factors, such as pre-stroke dependency and mental health, rather than differences in the organisation of subacute rehabilitation services.